Oligosaccharides as Green Catalyst for One-Pot Multicomponent Synthesis of Spirooxindole Derivatives in Water: Life Sciences-Chemistry for New drug discovery - Anand Mohan Jha; Nidhi Jha (International Journal of Life Science and Pharma Research, 2022)
A one pot synthetic methodology has been developed towards multicomponent synthesis of spiro[indoline-3,2'- quinazoline]-2,4'(3'H)-dione from isatoic anhydride, isatin and primary amines in aqueous medium via supramolecular catalysis. An untapped potential of β-Cyclodextrin to mediate multicomponent reactions in aqueous medium has been revealed. Developed protocol was further verified by extrapolating the synthetic protocol using different isatin derivatives and amine analogues. In other synthetic scheme, some compounds were synthesized by reaction of various substituted benzaldehydes, Isatoic anhydride and primary amines. Synthesized library of compounds were further characterized using various spectroscopic techniques. During all the synthetic process, the catalytic efficiency of cyclodextrin was exploited. Efficiency of all the three forms of cyclodextrins were tested to find the best reaction for synthesis of spiro compounds. The usefulness of β-cyclodextrin was proved by showing its reusability. The essential role of β-cyclodextrin in the synthetic methodology is further proved by doing the control experiments which showed that no product was formed in the absence of catalyst. The attachment of reactant molecule was also proved by doing 1H NMR of reaction mixture at different time interval in D2O. On the basis of observation, a plausible mechanistic pathway of reaction was proposed. Other two forms of cyclodextrins were also eliminated on the ground of their insuitability in the formation of desired product. Catalyst reusability was studied and it was shown that our catalytic system is useful without any significant loss in catalytic potential even after 5 cycles. Catalyst recovery procedure was established and was used without any significant loss of catalytic activity upto 5 times.